2022
DOI: 10.1021/acs.orglett.2c03612
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Mediated Synthesis of Phenanthrenes through Successive Photosensitization and Photoredox by a Single Organocatalyst

Abstract: An efficient approach for the synthesis of phenanthrene scaffolds by utilizing the dual catalytic activity of an organo-photocatalyst is documented. The controlled cascade transformation proceeds via in situ diazotization followed by olefin isomerization and subsequent arene radical generation through photoreduction. The overall process demonstrates both the photosensitization and photoredox properties of a single organo-photocatalyst and facilitates the desired intramolecular annulation with high precision an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…In this context, the development of synthesis of phenanthrene derivatives through one‐pot cascade reactions of readily available starting materials is of great value, because these compounds containing conjugated π‐systems have increasing applications in drug design and material development [9–14] . Among early developed methods for the synthesis of phenanthrenes, [15–39] the Scholl‐type oxidation reactions with stilbenes as substrates are the most widely used [25–29] . But these reactions usually require excessive strong acids and/or strong oxidants, thus resulting in unwanted side reactions and inseparable byproducts, leading to low reaction efficiency (Scheme 1b) [25–29] .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, the development of synthesis of phenanthrene derivatives through one‐pot cascade reactions of readily available starting materials is of great value, because these compounds containing conjugated π‐systems have increasing applications in drug design and material development [9–14] . Among early developed methods for the synthesis of phenanthrenes, [15–39] the Scholl‐type oxidation reactions with stilbenes as substrates are the most widely used [25–29] . But these reactions usually require excessive strong acids and/or strong oxidants, thus resulting in unwanted side reactions and inseparable byproducts, leading to low reaction efficiency (Scheme 1b) [25–29] .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, Scholl‐type oxidation generally prefers electron‐neutral arenes, but electron‐poor and highly electron‐rich/heterocyclic arenes are not suitable substrates. Photochemical Mallory‐Katz reaction features milder conditions, but the dilute reaction concentrations (∼10 −4 M) limit its synthetic potential [30–38] . The Dong's improvement in dehydrogenative cyclization of o ‐teraryls required complicated Co complexes as catalysts [39] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterocycles were also tolerated to give indanonederived phenanthrene 3la and thiophene derivative 3ma, which was found to be inaccessible through recently reported photocatalytic methods. 30 Next, we explored the styrene scope with representative aryl iodide coupling partners. We found that styrenes with various substitution patterns performed well under the reaction conditions.…”
mentioning
confidence: 99%
“…The disubstituted aryl iodides ( 1i – 1k ) delivered the trisubstituted phenanthrene cores ( 3ia – 3ka ) in good yields. Heterocycles were also tolerated to give indanone-derived phenanthrene 3la and thiophene derivative 3ma , which was found to be inaccessible through recently reported photocatalytic methods …”
mentioning
confidence: 99%